Pendampingan Perencanaan Desain Intake Air Bersih Desa Kalikayen Kecamatan Ungaran Timur Kabupaten Semarang - Wanto, Sri; Tutuko, Bambang; Haji, Son; Widorini , Trias; Widiatmoko, Kukuh Wisnuaji (Jurnal Pengabdian KOLABORATIF, 2026)
Clean water availability is a fundamental necessity that requires reliable Water Supply System (SPAM) infrastructure. Kalikayen Village, Ungaran Timur District, Semarang Regency, possesses considerable water resources that have not been optimally utilized due to the absence of an adequate technical design for a water intake structure. This community service program aimed to enhance the community’s capacity in planning a clean water intake structure while developing a preliminary design concept to support the village water supply system. The program employed advocacy, training, and technical assistance through a participatory approach, including field surveys, existing condition assessments, technical training, discussions, field observations, and evaluation using pre-tests and post-tests involving 20 participants. The evaluation results indicated a significant improvement in participants’ knowledge, with the average score increasing from 52.6% in the pre-test to 86.0% in the post-test, representing an improvement of 33.4 percentage points. In addition to strengthening community capacity, the program produced technical outputs, including a preliminary intake design, recommendations for a safer intake location, field survey data, and supporting documents that can serve as the basis for preparing a Detail Engineering Design (DED) and cost estimation. Overall, the program successfully improved community capacity while providing technical planning documents to support the development of a safe, reliable, and sustainable village water supply system.